Prediction of Fatigue and Rutting Premature Distress in Linear layered Flexible Pavements for Different Loading Condition using the Mechanistic-Empirical Method - Younis, Noor Y.; Khlil, Amina A.; Abdulmawjoud, Ayman A. (Sulaimani Journal for Engineering Sciences, 2021)
The research aims to study and analyze the damage to asphalt roads and load change based on (KENPAVE) program by evaluating the performance of flexible pavement using the Mechanistic-Empirical Method (M-E). A multi-layered structure for flexible pavement was assumed with load ratios of 50%, 100%, 150%, and 200% of the standard load according to Iraqi specifications. Depend on horizontal tensile strain at the bottom of asphalt layers to estimate the fatigue failure and on the vertical compressive strain above soil layers to estimate the rutting failure. Analysis of the results showed that the highest values of vertical stress were on the single axle in the wearing layer with a value of (639.753 KPa) for standard load, and the raising of load increased the pressure distributed by the vehicle to the pavement so that the tensile and compressive strain was higher. However, the lower tensile and compressive strain values increased both (Nf and Nr). The highest tensile strain values among the layers occurred at asphalt stabilized base coarse of the single axle of (-1.5*10-4) for the standard load. While the highest compressive strain values exist at the top of the subbase layer of the single axle with dual tires of (4.761*10-4) for the standard load. It was also observed that the increasing of axle loads produces an increase in the vertical displacement of the pavement, where the deformation value on the wearing layer of the tandem axle is (0. 8998 mm) for standard load, and that (84%) of this deformation was in the subgrade layer. However, the highest value of damage ratio was existing at the asphalt stabilized base coarse with a value of (0.04426) at standard load. It was also found that the design life decreases by 9 times when increasing the load twice the standard load, which in turn reduces the paving efficiency.
Keywords: Flexible Pavement; Mechanistic-Empirical Method; KENPAVE; Fatigue; Rutting